Childhood adiposity trajectories and risk of nonalcoholic fatty liver disease in adolescents. Issue 1 (January 2015) - Ayonrinde, Oyekoya T; Olynyk, John K; Marsh, Julie A; Beilin, Lawrence J; Mori, Trevor A; Oddy, Wendy H; Adams, Leon A
Abstract Background and Aim Nonalcoholic fatty liver disease (NAFLD) and its metabolic risk factors are recognized during childhood and adolescence. Identification of adolescents at risk of NAFLD from childhood anthropometry may expose opportunities to influence the hepatic and metabolic destinies of individuals. We sought associations between NAFLD diagnosed during adolescence and earlier life trajectories of anthropometry, in a population‐based cohort of predominantly Caucasian adolescents. Methods Assessment for NAFLD, using questionnaires and liver ultrasound, was performed on 1170 adolescents, aged 17 years, from the population‐based Raine cohort. We sought associations between NAFLD in adolescents and serial anthropometric measurements recorded from birth, childhood, and adolescence. Results NAFLD was diagnosed in 15.2% of adolescents. Birth anthropometry, including birth weight, skinfold thickness, and ponderal index, was not associated with NAFLD. However, adiposity differences between 17‐year‐old adolescents with NAFLD and those without NAFLD were apparent from age 3 years. Greater adiposity trajectories for weight, body mass index, skinfold thickness, mid‐arm circumference, and chest circumference from age 3 years onwards, particularly in males, were associated with the diagnosis of NAFLD and severity of hepatic steatosis at age 17 years (P < 0.05). The strength of the associations increased with age after 3 years for each adiposity measure (all P < 0.001). Conclusions Trajectories of childhood adiposity are associated with NAFLD. Adiposity attained by 3 years of age and older, but not at birth, was associated with the diagnosis and severity of hepatic steatosis in late adolescence. Exploration of clinically relevant risk factors and preventative measures for NAFLD should begin during childhood.